Study on Mechanical Properties of Polymer Composites Filled with Nano Egg-shell Powder - Subhrajit Ray; Sourajit Acharya; Prasanta Kumar Barik; Sonali Das (Archives of Current Research International, 2024)
Polymeric materials, when reinforced with synthetic fibers like glass, carbon, and aramid, offer notable advantages including increased stiffness and strength-to-weight ratio compared to conventional materials such as wood, concrete, and steel. Among these options, glass fiber stands out due to its affordability and widespread availability. Glass fiber reinforced polymer composites exhibit moderate mechanical properties, which can be significantly enhanced by incorporating nano fillers like eggshell powder. This study explores the utilization of nano eggshell powder as well as methods for effectively integrating nano fillers into polymer composites to create value-added products. Four types of composites, varying in weight proportions of nano eggshell powders, were prepared using the hand lay-up technique for mechanical and thermal characterizations. Various mechanical properties including tensile strength, flexural strength, impact behavior, as well as thermal properties via TGA and DMA analysis were investigated. The results indicate that incorporating the optimal amount of nano fillers significantly improves the overall strength of glass fiber reinforced composite materials, leading to cost savings of over 30%. This suggests that nano eggshell fillers hold great potential in composite manufacturing, particularly for substituting high-cost glass fibers in low load-bearing applications.